The dynamics of hedge fund share restrictions - Hong, Xin (Journal of Banking & Finance, 2014)
Nearly one in five hedge funds change their share restrictions (e.g., lockup) from 2007 to 2012. Using a large panel dataset, this paper is the first to empirically examine the incidence, determinants, and consequences of share restriction changes. We find that funds with high asset liquidity and low liquidity risk are more likely to decrease share restrictions and funds with good performance are more likely to increase share restrictions. A hazard model indicates that funds who actively manage liquidity concerns live longer by adjusting share restrictions. We examine whether changes in share restrictions create an endogeneity bias in the share illiquidity premium (Aragon, 2007) and find that 18% of the premium can be explained by the dynamic nature of contract changes.